Religious Tolerance in the Digital Age: A Discourse Analysis of the 'Log In' Podcast - Sasea, Sanita Carolina; Habibi, Ahmad Wildan; Dewi Anida Nurul, Fitroh (Citra Media Publishing, 2025)
The advancement of social media has changed the way religious messages are disseminated in society, including in the realm of da'wah. Digital platforms such as YouTube, Instagram, and TikTok have become new spaces for preachers to deliver lectures that emphasize the values of religious moderation and tolerance. This study aims to analyze how social media becomes a medium for da'wah discourse that supports interfaith harmony and how it affects patterns of social interaction in society. Using a qualitative approach based on discourse analysis, this research examines various da'wah content that emphasizes inclusive messages, interfaith dialogue, and calls for peaceful coexistence. The results show that social media is not only a means of spreading da'wah but also forming a new ecosystem for a more open religion. Preachers and preachers who are active on social media have a strategic role in building a more moderate religious narrative, so as to reduce the potential for religious-based conflict. In addition, audience interaction through online comments and discussion features shows a wider acceptance of tolerance values, although there are still challenges from conservative groups that maintain exclusive views. Thus, social media has the potential to be an effective instrument in building a more inclusive and harmonious understanding of religion amid the diversity of digital society.